A reliability assessment examining the inter- and intraobserver reliability of the current england and wales cricket board musculoskeletal profiling protocol. Issue 2 (20th January 2011) - Dacombe, Peter; Ranson, Craig; McCaig, Steve; Young, Mark
Abstract : Background: The England and Wales Cricket Board (ECB) musculoskeletal profiling was first introduced in 2005 and has been developed over the past four seasons with the aim of identifying risk factors for injury in elite level cricketers aiding both injury prevention and rehabilitation. The ECB Physiotherapy Team carries it out at six monthly intervals. The ability of such a tool to accurately predict injury risk, and to provide useful information for rehabilitation is entirely dependent on the ability to produce valid and reliable results. Study aim: To examine the inter- and intraobserver reliability of the current system in the hands of two experienced sports physiotherapists examining elite level cricketers. Methods: Using the prescribed testing protocol eight members of the England under 19 cricket squad were examined on two occasions by two sports physiotherapists who have worked in elite level cricket. Statistical analysis was carried out to determine the inter- and intraobserver reliability of the tests. Results: Of seven range of motion tests included in the study four showed 'almost perfect' reliability, an intraclass correlation coefficient of greater than 0.8, this level is reported to be an acceptable for screening in an elite sport setting. Only two of the tests examined demonstrated inter-rater reliability of greater than 0.8. Conclusion: The ECB musculoskeletal profiling system is crucial to early identification and modification of injury risk factors. It is well-designed and based on current sports injury literature, but can not be efficacious in the absence of reliable testing. Only two of the current tests have sufficient inter-observer reliability for use in screening elite sportsman, four demonstrating acceptable intraobserver reliability. One of the tests (modified Thomas test) demonstrated such poor reliability to question it's inclusion, this study highlights the need to investigate ways to improve the reliability of other tests in the profiling system.